Characterisation of residual stress state and distortion in welded plates stress engineered by local mechanical tensioning - Ganguly, Supriyo; Wescott, A.; Nagy, T.; Colegrove, Paul A.; Williams, Stewart W. (Transtec Publications; 1999, 2014)
Local mechanical tensioning is one of the most efficient and industrially relevant stress engineering techniques to modify weld residual stress field and subsequently reduce buckling distortion. However, application of rolling load and its magnitude need to be optimised for an energy efficient rolling process. In the present study gas metal arc butt welded plates of low carbon mild steel were rolled by a dual roller in different rolling configuration (top and reverse side rolling) and with different magnitude of rolling load. All the plates were rolled post welding. Residual strain profiles of the post weld rolled plates were measured, using the SALSA strain scanner, and the inplane stress were characterized. Average distortion of the rolled plates was correlated with the residual stress state. Reverse rolling was found to be more effective in removing distortion while the stress profile did not show any significant reduction of the peak stress.